Indicative features of tissue and microbial sensitization in the pathogenesis of generalized periodontitis associated with rheumatoid arthritis. - Kolenko Ю. Г.; Zelinska Н. А.; Dementieva О. В. (Actual Dentistry, 2024)
Relevance. A lot of research has been devoted to the pathogenesis of generalised periodontitis, but very often researchers do not take into account the fact that generalised periodontitis often ccurs against the background of internal diseases of the body, which cause not only special anifestations of the course of generalised periodontitis, but also can affect the results of its prevention and treatment. In this sense, rheumatoid arthritis, which is accompanied by chronic systemic connective tissue damage, is noteworthy. Purpose: to determine the place and integrative features of tissue and microbial sensitisation in the pathogenesis of generalised periodontitis associated with rheumatoid arthritis. Material and methods of the study. Immunological studies were performed in 335 patients, divided into 3 groups: Group 1 — the main group — consisted of 136 patients with GP in the setting of RA. Group 2 — control group — 71 patients with GP diseases without signs of RA. Group 3 — comparative — 128 people without GP disease, who had musculoskeletal diseases not related to RA and practically healthy people. The periodontal condition of patients was assessed in two groups using the following parameters: Silness-Loe index (PI), bleeding index (BOP), probing pocket depth (PPD), recession level (REC), clinical attachment level (CAL) and tooth loss. To determine microbial and tissue sensitisation, the leukocyte migration inhibition reaction was used with microbial antigens of streptococci and staphylococci, and tissue antigens (bone and synovial). All the data obtained was processed by the mathematical method of variation statistics. Results of the study. In the majority of patients with GP affiliated with RA, a pronounced sensitisation to streptococcal antigen was detected, which in the chronic course of GP was 70.3, 4.3%. The acute course in this group was accompanied by a high level of sensitisation in a slightly lower percentage of patients in this group and amounted to 62.5 ± 7.0%. In the control group, the frequency of sensitised individuals to streptococcal antigen was significantly lower and amounted to 37.5 ± 8.9 in the chronic course and 44.0 ± 6.1 in the acute course. In practically healthy people without pathology of internal organs, musculoskeletal system and without GP disease, this indicator was only 26.0 ± 8.0. Conclusion. The presence of microbial and tissue sensitisation in patients with GP and RA indicates that similar and cross antigens of streptococcus and staphylococcus microorganisms with connective tissue are a potential trigger for the development of both GP and RA, which is the reason to consider GP and RA as comorbid diseases with similar pathogenetic mechanisms of development.